Comparison of transabdominal wall specimen retrieval and natural orifice specimen extraction robotic surgery in the outcome of colorectal cancer treatment - Houqiong, Ju; Ziwen, Wan; Chonghan, Zhong; Penghui, He; Hongxin, Yu; Weijie, Lu; Dongning, Liu; Taiyuan, Li (Frontiers in Surgery, 2023)
Abstract Background Natural orifice specimen extraction surgery (NOSES), as a new star of minimally invasive techniques, has been increasingly favored and promoted in the field of surgery around the world. Most previous studies were comparative studies of laparoscopic NOSES and conventional laparoscopic surgery. However, there is little research on comparing robotic colorectal cancer NOSES with conventional robotic-assisted colorectal cancer resection surgery. Participant and Methods This study is a retrospective study of propensity score matching(PSM). This study included Ninety-one propensity score-matched pairs of the participant who had undergone robotic colorectal cancer resection surgery at our center between January 2017 and December 2020. The covariates used in the propensity score included gender, age, BMI, ASA score, maximum tumor diameter, the tumor's height from the anal verge, histological differentiation, AJCC stage, T stage, N stage, and history of previous abdominal surgery. The outcome measurement criteria included postoperative complications, inflammatory response, pelvic floor function, anal function, cosmetic outcome, quality of life, disease-free survival (DFS), and overall survival (OS). Results The robotic NOSES group had faster recovery time from gastrointestinal function (P = 0.014), shorter abdominal incision length (P < 0.001), less pain (P < 0.001), less additional analgesia required (P < 0.001), and lower postoperative indicators of white blood cell count (P < 0.001) and C-reactive protein content compared to the robotic-assisted resection surgery(RARS) group (P = 0.035). Additionally, the robotic NOSES group had significantly better body imagery (P < 0.001), cosmetic scores (P < 0.001), somatic function (P = 0.003), role function (P = 0.039), emotional function (P = 0.001), social function (P = 0.004), and overall function (P < 0.001) than the RARS group. The two groups demonstrated no significant difference between DFS and OS. Conclusion Robotic colorectal cancer NOSES is a safe and feasible minimally invasive procedure and offers shorter abdominal incisions, less pain, less surgical stress response, and better postoperative quality of life. Therefore, this technique can be further promoted for colorectal cancer patients eligible for NOSES.